Changes in insulin resistance following antidepressant treatment mediate response in major depressive disorder. (March 2023) - Rashidian, Houman; Subramaniapillai, Mehala; Park, Caroline; Lipsitz, Orly; Zuckerman, Hannah; Cao, Bing; Lee, Yena; Gill, Hartej; Rodrigues, Roger Nelson; Di Vincenzo, Joshua D.; Iacobucci, Michelle; Jaberi, Saja; et al.
Background: Insulin resistance (IR) is a potential predictor of antidepressant treatment response. Aims: We assess changes in IR after antidepressant treatment and whether these changes have any effect on treatment response. Also, to see whether changes in IR mediates relationship between C-reactive protein (CRP) and antidepressant efficacy. Methods: This is a secondary analysis of an 8-week, open-label clinical trial with 95 adults experiencing a major depressive episode. Response to vortioxetine was measured using the Montgomery–Åsberg Depression Rating Scale (MADRS). Generalized estimating equation models were utilized for this intent-to-treat analysis. Results: When adjusted for age, sex, and body mass index, there was a significant increase in IR following treatment in the overall sample (p = 0.035). This finding was detected in treatment non-responders (p = 0.019), whereas it was not observed in responders (p = 0.329). Mediation analysis revealed that change in IR during treatment was responsible for change in MADRS as well as the relationship between baseline CRP and treatment response. Conclusions: Exacerbation of IR during antidepressant treatment mediated non-response. Conversely in treatment responders IR reduced. Like previous studies, baseline CRP moderated treatment response. This relationship was also mediated by changes in IR. These findings further elucidate the role of IR in terms of antidepressant response as well as potentially explain inflammation's relationship with the latter.